Palliative Referrals in Advanced Cancer Patients: Utilizing the Supportive and Palliative Care Indicators Tool and Rothman Index. (February 2022) - Chan, Abigail Sy; Rout, Amit; 'Adamo, Christopher R. D.; Lev, Irina; Yu, Amy; Miller, Kenneth
Background: Timely identification of palliative care needs can reduce hospitalizations and improve quality of life. The Supportive & Palliative Care Indicators Tool (SPICT) identifies patients with advanced medical conditions who may need special care planning. The Rothman Index (RI) detects patients at high risk of acutely decompensating in the inpatient setting. SPICT and RI among cancer patients were utilized in this study to evaluate their potential roles in palliative care referrals. Methods: Advanced cancer patients admitted to an institution in Baltimore, Maryland in 2019 were retrospectively reviewed. Patient demographics, length of hospital stay (LOS), palliative care referrals, RI scores, and SPICT scores were obtained. Patients were divided into SPICT positive or negative and RI > 60 or RI < 60.Unpaired t-tests and chi-square tests were utilized to determine the associations between SPICT and RI and early palliative care needs and mortality. Results: 227 patients were included, with a mean age of 68 years, 63% Black, 59% female, with the majority having lung and GI malignancies. Sixty percent were SPICT +, 21% had RI < 60. SPICT + patients were more likely to have RI < 60 (p = 0.001). SPICT + and RI < 60 patients were more likely to have longer LOS, change in code status, more palliative/hospice referrals, and increased mortality (p <0.05). Conclusions: SPICT and RI are valuable tools in predicting mortality and palliative/hospice care referrals. These can also be utilized to initiate early palliative and goals of care discussions in patients with advanced cancer.